Cardiac Surgery of Complicated Forms of Coronary Artery Disease: Features of the Perioperative Period in High-Risk Patients - Gogayeva, Olena (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To analyze the features of the perioperative period in high-risk patients with complicated forms of coronary artery disease (CAD). Material and methods. Retrospective analysis of 160 patients with CAD who were operated and discharged from the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine in the period from January 2009 to December 2019. All the patients underwent electrocardiography, echocardiography, coronary ventriculography and surgical revascularization with correction of concomitant cardiac pathology. Results. One hundred thirty two (37.2%) patients were diagnosed with postinfarction left ventricular aneurysm (LVA), 12 (3.3%) with mitral regurgitation of ischemic origin, 16 (4.5%) patients had combination of CAD with aortic valve stenosis. Risk stratification by the ES II scale revealed the average risk of death of 10.08%. Surgery was performed in all the patients on day 5.7±4.7 of hospitalization. In 159 (99.3%) patients the operations were on-pump. There weak was direct correlation (r =0.29) between the dependence of the length of stay in the intensive care unit and the initial severity of the patient’s condition by the ES II scale. A weak direct correlation was found between the severity of the patient’s condition by the scales ES II (r =0.24, p=0.0022), STS (r =0.16, p=0.0325) and the time of discharge which was on 9.5±5.06 days in average. All the interventions were performed by experienced cardiac surgeons, with 25.3±14.1 years of experience in surgical treatment of CAD. Conclusions. Despite the high predicted mortality, 10.08% by the ES II scale, mortality in the studied group was 0%. In order to prevent complications, the management of patients in the perioperative period requires a clear algorithm of action and timely compensation of comorbidity at all stages of the patient’s stay in the cardiac surgery facility.